2008
DOI: 10.1001/archophthalmol.2007.61
|View full text |Cite
|
Sign up to set email alerts
|

Topical Omega-3 and Omega-6 Fatty Acids for Treatment of Dry Eye

Abstract: To study the efficacy of topical application of alpha-linolenic acid (ALA) and linoleic acid (LA) for dry eye treatment.Methods: Formulations containing ALA, LA, combined ALA and LA, or vehicle alone, were applied to dry eyes induced in mice. Corneal fluorescein staining and the number and maturation of corneal CD11b ϩ cells were determined by a masked observer in the different treatment groups. Real-time polymerase chain reaction was used to quantify expression of inflammatory cytokines in the cornea and conj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
163
0
7

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(179 citation statements)
references
References 36 publications
9
163
0
7
Order By: Relevance
“…The ω-6 origin of PGE1 and TXA1 via cyclooxygenase 1 (COX1) and the effects of the ω-3 fatty acids eicosapentaenoic acid and docosapentaenoic acid could explain the clinical improvements in the animals that received the linseed oil treatment (18,19) . These results are in agreement with a previous study that used a topical formulation containing an emulsion of alpha-linolenic acid and linoleic acid on mice with experimentally induced KCS; the inflammatory symptoms of KCS improved in the mice (17) . A recent study compared almond and linseed oil as diluents of tacrolimus, another immunosuppressor, in the treatment of KCS in rabbits and showed that linseed oil either as a diluent or in isolation was more effective than almond oil (16) .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The ω-6 origin of PGE1 and TXA1 via cyclooxygenase 1 (COX1) and the effects of the ω-3 fatty acids eicosapentaenoic acid and docosapentaenoic acid could explain the clinical improvements in the animals that received the linseed oil treatment (18,19) . These results are in agreement with a previous study that used a topical formulation containing an emulsion of alpha-linolenic acid and linoleic acid on mice with experimentally induced KCS; the inflammatory symptoms of KCS improved in the mice (17) . A recent study compared almond and linseed oil as diluents of tacrolimus, another immunosuppressor, in the treatment of KCS in rabbits and showed that linseed oil either as a diluent or in isolation was more effective than almond oil (16) .…”
Section: Discussionsupporting
confidence: 93%
“…Some authors have reported the treatment of experimentally induced KCS in rabbits using linseed oil in various preparations (oral, topical, and oral/topical combination) (15,16) . In mice with experimentally induced KCS, the topical use of ω-3 and ω-6 has been shown to successfully control inflammatory symptoms (17) . Linseed oil is considered a natural anti-inflammatory agent due to its potential for synthesizing noninflammatory mediators, such as prostaglandin E1 (PGE1) and thromboxane A1 (TXA1) (18,19) .…”
Section: Comparison Of 1% Cyclosporine Eye Drops In Olive Oil and In mentioning
confidence: 99%
“…The role of this marker in ocular inflammation is still unknown, even when the existence of this inflammatory marker had already been reported in the cornea of a dry eye animal model, which was the result of leukocytic infiltration and activation. 33 The decrease we discovered in both groups could be There is only one study that determines the effect of an additional treatment after cataract surgery on dry eye signs and symptoms; however, it does not involve artificial tears, but rather cyclosporin A 0.05% twice a day 1 month preoperatively and 1 month post-operatively, resulting in an improvement in symptoms (in a nonvalidated questionnaire) but not in TBUT, which did not improve in the group receiving CyA. 34 A recent study has shown similar results adding CyA after trabeculectomy, improving OSDI index with neither TBUT nor Schirmer test values improvement.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used techniques are PRK and LASIK, both of which damage the corneal nerves. Clinical studies using confocal microscopy to measure corneal nerve density following these procedures have reported that it took 2 years for patients to recover 80% of the original nerve density after PRK, whereas after LASIK (in which there is nerve damage at the stromal level) it took almost 5 years to obtain an meibomian gland dysfunction ( 127,128 ). Elevated gene expression of interleukin (IL)-1, IL-6, IL-8, and TNF ␣ in the conjunctival epithelium and a higher tear concentration of IL-1 has been reported in patients with dry eye ( 129,130 ).…”
Section: -3 Fatty Acids and Their Derivatives Are Important In The Rementioning
confidence: 99%